Nutrients affecting food choice by the pest subterranean termite Coptotermes gestroi (Isoptera: Rhinotermitidae) - Haifig, Ives [UNESP]; Marchetti, Fabio Frattini [UNESP]; Costa-Leonardo, Ana Maria [UNESP] (Taylor & Francis Ltd, 2010)
Coptotermes gestroi is a subterranean termite from Asia, introduced accidentally to Brazil, where it is responsible for substantial damage in urban areas. The foraging range of this species frequently overlap with that of Heterotermes tenuis, a native termite also considered to be a severe pest. The greatest challenge in controlling these termites is to develop baits suitable for both species. A critical issue is to select compounds that act as common phagostimulants. We examined whether the feeding preferences of C. gestroi for some nutrients were similar to those already reported for H. tenuis. A double choice design was used. Consumption was evaluated by change in the dry mass of paper discs after termite feeding. C. gestroi fed preferentially on discs treated with a solution of sucrose+yeast. However, insects did not choose urea at 0.015g/ml, one of the preferred solutions for H. tenuis. These results indicate that the two termites have different feeding preferences, and we suggest future use of sucrose+yeast in baits for management of C. gestroi.
Keywords: bait; phagostimulant; termite; sugar; urea